Digitalization, immigration and the welfare state - Blix, Mårten 1968- (Edward Elgar Publishing, 2017)
The Swedish welfare state finds itself in the middle of two major upheavals: The impact of technology and immigration. Having taken in more refugees per capita than most other countries, the pillars of the welfare state are being shaken. Digital technologies are set to strengthen already existing trends towards job and wage polarization. This book explores how these trends are more pronounced due to the rigidity of the labor market and the comprehensiveness of tax-financed welfare services
Keywords: Wohlfahrtsstaat; Einwanderung; Sozialstaat; Digitalisierung; Schweden; Welfare state / Sweden